Thermal Characteristics and Kinetics of the Thermal Degradation of Sugar Beet Waste Leaves and Pulp in Relation to Chemical Composition - Sanja Ostojić; Darko Micić; Josipa Dukić; Iva Sabljak; Ayça Akyüz; Seda Ersus; Anet Režek Jambrak (Foods)
Thermal characteristics of dried sugar beet pulp, leaves and leaf fractions obtained after extraction: fibrous leaf pulp and fibre rich leaf fraction, were investigated by differential scanning calorimetry and thermogravimetry. The sugar beet samples showed a similar thermal behaviour associated with a similar composition. Two endotherms are found on the differential scanning calorimetry curves. First one in the temperature range 31–153 °C and the second from 150–160 °C. Thermal degradation kinetics was studied by thermogravimetric analysis. Four degradation stages were observed within the temperature range 25–700 °C. The kinetic parameters of the degradation, obtained by Ortega and Friedman non-isothermal isoconversional methods did not significantly differ between models: Ea-activation energy at a conversion degree 0.1–0.9 ranged 50–200 kJ/mol; lnA- the natural logarithm of the pre-exponential factor 8–48; kp1-thermal degradation rate constant at a conversion extent of 0.5 ranged of 0.19–2.55 min−1. Constant rate of degradation is highest for the sugar beet leaves kp1 (2.58–2.55 min−1), and kp2 (70.1–70.4 min−1). The results obtained are valuable for sugar beet leaf industrial processing. A positive environmental impact is achieved by transforming the waste into high-value food additives.